Antidiabetic and antioxidant potentials of commercial and traditional bran extracts of Malaysian rice varieties - Sadiq, Tanko Abubakar (2016)
Malaysian traditional rice varieties are believed to have more nutraceutical values than the commercial rice varieties. This study intended to compare the anti-diabetic potentials, total poly phenolic contents and antioxidant activities of bran extracts of seven Malaysian traditional rice varieties (Adan halus, Adan kasar, Salleh halus, Salleh Kasar, Beras merah, Beras hitam and Nanung) with those of three commercial varieties collected from Selangor, Kedah and Perlis. About 10 grams of the dried rice bran samples were extracted successively with 70% ethanol (3x100 mL) by overnight soaking to obtain ethanolic extracts, which were subsequently concentrated under reduced pressure using rotary evaporator. α-amylase and α-glucosidase inhibitory potentials of the rice bran extracts (RBEs) were studied in vitro. The total polyphenolic contents (TPC) and antioxidant activities (FRAP, ABTS and DPPH) of the crude extracts were also determined in vitro. Beras merah and Beras hitam showed α-glucosidase inhibition of 96.56 % ± 0.58 and 81.52 % ± 0.96, α-amylase inhibition of 88.44 % ± 3.41 and 84.27 % ± 3.02, and total poly phenolic content of 14.94 ± 0.53 and 10.22 ± 0.25 mg Gallic acid equivalent /g of dry rice bran respectively while the commercial rice brans displayed alpha amylase inhbition of [Kedah (72.5± 0.54% ), Perlis (66.0% ± 2.72) and Sekinchan (69.4% ± 3.02)] and alpha glucosidase of [Kedah (86.9% ± 0.51), Perlis (48.2% ± 1.13) and Sekinchan (70.5% ± 2.40)]. The commercial bran extracts of the rice varieties (Kedah, Perlis and Sekinchan) showed antioxidant activities of [FRAP (1.7 ± 0.3 1.8 ± 0.0 and 1.6 ± 0.0 mmol FeSO4/1 g bran ), ABTS (0.2 ± 0.0 0.2 ± 0.0 and 0.3 ± 0.0 mmol Trolox/1 g bran) and DPPH (1.1 ± 0.4 2.5 ± 0.0 and 2.4 ± 0.0) mmol Trolox/1 g bran]. The results showed that the traditional varieties (RBEs of Beras merah and Beras hitam) displayed significant enzyme inhibitory and antioxidant activities than the bran extracts of the commercial rice bran varieties. These two traditional RBEs found to display significantly (p<0.05) higher enzyme and antioxidant activities were tested for their antidiabetic potentials in vivo on normal and diabetic Sprague Dawley rats at two different concentrations (400 mg/kg and 200 mg/kg each). The results indicated that the extracts possess antidiabetic potentials with Beras merah having better potency than Beras hitam especially at 400 mg/kg. This was seen in the abilities of the rice bran extracts to lower the blood glucose levels of both the normal and diabetic rats as well as restore other biochemical markers like plasma alanine amino transferase (ALT) and blood triglycerides (TAG). The results indicated that brans of traditional rice varieties such Beras merah, and Beras hitam possess better potency as antioxidants and anti-diabetic agents than the commercial rice brans,hence could be used as good sources of natural anti-diabetic and antioxidants agents.